Program ‘BERANI’ UNICEF dalam Pengentasan Kasus Perkawinan Anak di Kabupaten Bone Sulawesi Selatan - Allo, Janelsy Bali (Journal of International and Local Studies, 2025)
Child marriage is one of the problems currently faced by Indonesia, with a relatively high rate of child marriage. This study discusses UNICEF's “Berani” Program in eradicating child marriage cases in Bone Regency, South Sulawesi. The author uses a qualitative research method with the aim of describing the research results. The types and sources of data used are primary and secondary, with data collection techniques including in-depth interviews with informants and literature reviews. The research findings indicate that UNICEF has successfully reduced the percentage of child marriages in Bone District, South Sulawesi, by collaborating with multiple sectors to develop policies through the Child Marriage Prevention Strategy Program (SIP-PEKA). This program collaborated with UNICEF and other institutions, ultimately reducing the number of child marriages, which stood at 748 cases in 2019. This figure decreased as 372 villages and neighborhoods in Bone received information about preventing child marriage, resulting in only 84 cases of child marriage in 2021.